Environmental context of endophyte symbioses: Interacting effects of water stress and insect herbivory - Miranda, M. Isabel (2011)
Symbiotic associations between grasses and fungal endophytes are generally regarded as mutualistic, yet benefits to host plants may vary with environmental context. Previous studies have emphasized how endophytes influence plant responses to single stressors. In contrast, the outcome of endophyte-grass interactions under simultaneous biotic and abiotic stresses remains poorly explored. We hypothesized that benefits from endophyte symbiosis become most apparent in "complex" environments where hosts experience multiple stresses. We evaluated the performance of endophyte-infected (E+) vs. endophyte-uninfected (E-) Lolium multiflorum plants in a factorial experiment with water supply (control vs. drought) and insect herbivory (with aphids vs. without aphids). Endophyte infection delayed tiller production in well-watered plants, while water stress reduced tillering in E- plants. Endophyte mediation of herbivory tolerance was contingent on water supply. Whereas aphid herbivory was detrimental to E+ plants in well-watered soils, aphids interacted with drought stress in decreasing the reproductive output of E- but not E+ plants. Moreover, endophyte presence decreased aphid densities on drought-stressed plants only. Thus, endophyte symbiosis enhanced host tolerance to overlapping biotic and abiotic stresses, although infected plants failed to outgrow their uninfected counterparts. These results support the view that mutualistic endophyte effects may not arise in low-stress environments. © 2011 by The University of Chicago. All rights reserved.